2002
DOI: 10.1152/japplphysiol.01271.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes of lung diffusing capacity and tissue volume in hypergravity

Abstract: In normal gravity, lung diffusing capacity (DL(CO)) and lung tissue volume (LTV; including pulmonary capillary blood volume) change in concert, for example, during shifts between upright and supine. Accordingly, DL(CO) and LTV might be expected to decrease together in sitting subjects in hypergravity due to peripheral pooling of blood and reduced central blood volume. Nine sitting subjects in a human centrifuge were exposed to one, two, and three times increased gravity in the head-to-feet direction (G(z+)) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
(28 reference statements)
1
30
2
Order By: Relevance
“…For very shortlasting microgravity, Vaida et al (30) showed that both DL NO and the membrane component of DL CO were increased by Ͼ40%. Furthermore, Rohdin et al (21) showed that DL CO is decreased by 21% at two times normal gravity (2 G) and by 34% at three times normal gravity (3 G) (21). We therefore exposed healthy subjects to both decreases and increases of gravity and studied their exhaled NO.…”
mentioning
confidence: 96%
“…For very shortlasting microgravity, Vaida et al (30) showed that both DL NO and the membrane component of DL CO were increased by Ͼ40%. Furthermore, Rohdin et al (21) showed that DL CO is decreased by 21% at two times normal gravity (2 G) and by 34% at three times normal gravity (3 G) (21). We therefore exposed healthy subjects to both decreases and increases of gravity and studied their exhaled NO.…”
mentioning
confidence: 96%
“…Cardiac effects of hypergravity include a 1 cm downward movement of the heart at 2.5 G (Rushmer 1947) and a 70% increase in its stroke work at 2 G compared to 1 G (Howard 1965). SV decreases by 20% whereas decreases in ð _ QÞ range from slight to large in different reports (Lindberg et al 1960;Rohdin and Linnarsson 2002;Rohdin et al 2004). These reports of SV and ð _ QÞ changes are in accordance with our results.…”
Section: Effect Of 2 G Without Anti-g Suit Inflationmentioning
confidence: 83%
“…For example, stroke volume (SV) is not constant during all phases of a parabola (increased during 0 G and decreased during 1.5-2 G [Johns et al 1994;Rohdin and Linnarsson 2002]), which renders difficult a comparison between cardiovascular data (Linnarsson et al 1996) and the study of cardio-pulmonary interactions (Lauzon et al 1997(Lauzon et al , 1998 at 0, 1 and 2 G.…”
Section: Introductionmentioning
confidence: 99%
“…Rohdin and Linnarson found increased lung tissue volume in healthy subjects during 2 and 3 G z centrifugation in a sitting position. Furthermore, they reanalyzed the parabolic flight data of Vaida et al and noted an increase in lung tissue volume in weightlessness (Vaida et al 1997; Rohdin and Linnarsson 2002). Vaida had performed the experiment during parabolic flights in the former European Caravel parabolic flight airplane under a hypobaric ambient pressure of 793 mbar.…”
Section: Discussionmentioning
confidence: 99%